Effective management of object social housing concrete products (with practical experience ICP "HBH-3 in 2012) - Bondar, I.; Savenko, V. (Ways to Improve Construction Efficiency, 2018)
Considered four options for social housing construction projects of concrete products concrete plant ICP "HBH-3."